Metallmatrixverbunde mit Verstärkungselementen aus metallischem Glas Ni??Nb??Ta?? - Herstellung und Charakterisierung - Lichtenberg, Klaudia (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2018)
AlSi12-based metal matrix composites using metallic glass Ni??Nb??Ta?? as reinforcement were produced via gas pressure melt infiltration technique. Comprehensive investigations were performed to determine the composite´s microstructural, mechanical and thermal properties as well as damage mechanisms. The results contribute to a better understanding on the material´s processing-structure-property relations.